Pengaruh Limbah Tomat dan EM4 terhadap Percepatan Pengomposan Limbah Baglog Jamur Tiram dalam Upaya Pembuatan Brosur bagi Masyarakat - Widianti, Novita (Biocaster : Jurnal Kajian Biologi, 2023)
Tomato fruit waste is fruit that has rotted and eventually becomes waste, often causing problems for the environment, so it is not widely used by the community. Tomato fruit waste can be used as a substitute for EM4 in making solid organic fertilizer, because in tomato waste there are microbes that can help the fermentation process. The aim of this research was to determine the effect of tomato waste and EM4 on accelerating the composting of oyster mushroom baglog waste. This type of research is experimental, namely there is 1 control and 2 treatments with 3 repetitions for each treatment so that 9 experimental plots are obtained. The research design used was a Completely Randomized Design (CRD). Data collection techniques use observation and documentation methods, then analyzed using descriptive methods. This was done to obtain fertilizer indicator data. Measurement of fertilizer indicators such as temperature, aroma, texture, color, pH and humidity. This research was carried out for 14 days and obtained data results which stated that tomato fruit waste was effective as a substitute for the role of EM4 in the process of making solid organic fertilizer, because in tomato fruit waste there are bacteria that help the fermentation process. The conclusion of this research is that the use of tomato fruit waste in the process of making organic fertilizer from oyster mushroom baglog waste produces good quality fertilizer as seen from the results of physical tests which show the characteristics, namely blackish brown color, odorless, neutral pH, humidity 60%-80 %, and the texture breaks down. The results of data analysis on the development of teaching materials showed that the validator score for teaching materials experts was an average of 4.6, material experts had an average of 4, and the public readability test average was 4.1, so that teaching materials in the form of brochures are suitable for use.